2009
DOI: 10.1159/000193146
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Right Ventricular Systolic and Diastolic Function in Patients with Newly Diagnosed Obstructive Sleep Apnea Syndrome without Hypertension

Abstract: Objectives: We investigated right ventricular (RV) structural and functional cardiac alterations in obstructive sleep apnea (OSA) independent of systemic hypertension and their correlation to the severity of OSA. Methods: Forty-one moderate-to-severe OSA but otherwise healthy patients and 30 body mass index-matched control subjects were included. All subjects underwent 24-hour ambulatory blood pressure monitoring, standard and tissue Doppler imaging of the RV. Results: The OSA group had increased RV wall thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 59 publications
1
24
0
3
Order By: Relevance
“…Untreated sleep apnea in patients with severe apnea causes a 46% excess mortality over 8 years, an increase attributed chiefly to increases in cardiovascular mortality [2]. OSA has been associated with impaired RV function despite normal systemic pressures [3]. The prevalence of OSA was estimated from large population studies such as the Sleep Heart Health study at up to 18% [4], although overt prevalence is reported at 4% of men and 2% of women [1].…”
Section: Introductionmentioning
confidence: 99%
“…Untreated sleep apnea in patients with severe apnea causes a 46% excess mortality over 8 years, an increase attributed chiefly to increases in cardiovascular mortality [2]. OSA has been associated with impaired RV function despite normal systemic pressures [3]. The prevalence of OSA was estimated from large population studies such as the Sleep Heart Health study at up to 18% [4], although overt prevalence is reported at 4% of men and 2% of women [1].…”
Section: Introductionmentioning
confidence: 99%
“…SDB was not assessed with polysomnography, and the sensitivity and specifi city of the questions used are not clear, so residual confounding could be present. [37][38][39][40] MESA excluded individuals with weight . 300 pounds, so that morbidly obese individuals in the study may have been less than those in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…As hypoxia and pulmonary HT are associated with OSA, right heart failure is likely to establish. Accordingly, attenuated RV contractility as well as impaired RV ejection fraction and hypertrophy have all been demonstrated in OSA patients in the absence of concomitant chronic obstructive pulmonary disease and HT (55).…”
Section: Cardiovascular Mechanisms Of Hf In Osamentioning
confidence: 99%